The Decrease In Number Of Blood Polymorphonuclear (Pmn) To Periapical Radiographs Dose Of radiation exposure - Adlina, Amni; Wasilah, Wasilah (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2012)
Periapical radiograph is a type of radiographic examinations that iswidely used in the field of dentistry. Radiographic X-ray is an ionizing radiationthat can cause damage and death to cells, tissues or organs, including thepolymorphonuclear (PMN). PMN is cell that serves as the first line of defenseagainst the invasion of organisms. Objective:The purpose of this study is 1) todetermine whether there is a decrease in the number of peripheral blood PMNafter being given periapical radiograph dose of X-ray radiation exposure, and 2)to determine whether there is any difference in the declining number of peripheralblood PMN after being given a single dose and some different total dose ofperiapical radiograph of X-ray radiation exposure. Methode: The design of thisstudy is an experimental laboratory research with total sample of 24 strains ofBalb c male mice. The sample is divided into four groups, each consisting 6 mice.Group 1 serves as the control group; Group 2 is given a treatment with a singledose exposure of periapical radiographs of X-ray radiation; Group 3 is given atreatment of 6 times total doses exposure of periapical radiograph of X-rayradiation; and Group 4 is given a treatment of 14 times total doses exposure ofperiapical radiograph of X-ray radiation. After 24 hours of radiation exposure, theblood was drown. Conclusion :The calculation is done by multiplying the numberof PMN percentage from leukocyte counts with a total leukocyte. The dataobtained are statistically tested using One Way Anova and LSD with asignificance level of 95%. Result :The result of this study indicates that there is adifference in the peripheral blood PMN counts in male mice after being exposedto radiation doses of periapical radiographs in all groups (P 0.05). There is anincreasing number of peripheral blood PMN in male mice after being treatedwithX-ray radiation at a single dose of periapical radiographic exposure, whereas afterbeing exposed with radiation at the dose of 6 and 14,the number of PMN isdeclining.The highest decreasing number of PMN isfound in the group withexposure of radiation at 14 dose.